A defect-rich transition metal oxide nanosheet / metal heterojunction catalyst and its preparation method and application
By introducing and regulating the defects of transition metal oxide nanosheets under low temperature conditions, defect-rich transition metal oxide nanosheets/metal heterojunction catalysts were prepared, which solved the problem of harsh reaction conditions in existing defect engineering technologies, and achieved the maintenance of nanosheet structure and the improvement of photothermal catalytic performance.
Patent Information
- Application Number
- CN202211391482.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-11-07
AI Technical Summary
The reaction conditions in the existing defect engineering technology are harsh, requiring high temperature and reducing agents, which can easily destroy the nanosheet structure and limit its application in the field of photocatalysis.
The defects of transition metal oxide nanosheets are introduced and regulated under low temperature conditions by metal catalysis, and defect-rich transition metal oxide nanosheets/metal heterojunction catalysts are prepared by controlling the metal precursor content and light time.
The introduction and regulation of nanosheet surface defects under mild conditions is achieved, the integrity of nanosheet structure is maintained, the light absorption range is expanded, the performance of photothermal catalytic oxidation of aromatic alcohol to aldehyde coupling is improved, and fine chemicals and clean hydrogen energy are produced simultaneously.
Smart Images

Figure CN116020458B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysis in energy, and in particular relates to a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, two-dimensional materials with unique structural characteristics and surface properties have become a research hotspot in the field of photocatalysis. Compared with traditional bulk materials, two-dimensional materials with only a single layer or a few layers of structure greatly shorten the carrier transmission distance and promote the efficient separation of electron-hole pairs. In addition, two-dimensional materials provide a larger specific surface area and more reactive sites, which are conducive to the adsorption and activation of reactant molecules. However, the low solar energy utilization rate of two-dimensional materials still greatly limits their application in the field of photocatalysis.
[0003] Defect engineering is a cutting-edge research topic in the field of catalysis and energy storage in recent years. Through defect engineering, the light absorption characteristics, electronic structure and other physical and chemical properties of nanomaterials can be regulated. For example, oxygen vacancies, as common defects in metal oxides, can induce an intermediate band gap in the band gap of metal oxide semiconductors, thereby narrowing the band gap width of the semiconductor and expanding its light absorption range. Therefore, introducing defect structures in nanomaterial photocatalysts to achieve functional customization is an effective strategy to further improve their catalytic performance.
[0004] Two-dimensional materials have a large specific surface area, which is conducive to the generation of surface defects, and their ultra-thin structure can reduce the generation of bulk defects, making them an ideal defect regulation material. However, common defect engineering usually uses high-temperature H2 atmosphere calcination, plasma activation, and strong reducing agent reduction, which consumes a lot of energy and is difficult to operate. In addition, such methods will have an adverse effect on the layered structure of two-dimensional materials. For example, high temperature conditions will cause the nanosheets to restack into a block structure, and severe reduction treatment will break the nanosheet structure into particles, hindering the further application of catalysts. Therefore, it is particularly important to develop an effective strategy to introduce and regulate surface defects of nanosheets under mild conditions.
[0005] The patent "Flake-like molybdenum carbide / transition metal heterojunction electrocatalytic composite material and its preparation method" with publication number CN110180569A provides a flake-like molybdenum carbide / transition metal heterojunction electrocatalytic composite material with excellent electrocatalytic performance synthesized by a one-step reaction through reducing gas under heating conditions. However, during the implementation of this method, the size of the carbon substrate needs to be adjusted according to the size of the specific reactor to ensure that it can be arranged around the side wall of the container so that the raw material can grow on the carbon substrate; the patent "A defect-rich Co3S4 ultra-thin porous nanosheet material and its preparation method and application" with publication number CN110404562A, the present invention uses plasma technology to treat inorganic-organic hybrid precursors with alternating inorganic and organic layers to dry-strip and prepare non-layered transition metal-based defect-rich ultra-thin porous two-dimensional nanosheet materials. However, in the preparation process of the present invention, the precursor needs to be treated with argon plasma to remove the organic layer in the inorganic-organic hybrid precursor, otherwise the organic component will have an adverse effect on the catalytic activity in subsequent electrochemical tests. Summary of the invention
[0006] The present invention introduces a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst and a preparation method and application thereof. Aiming at the deficiencies in the traditional defect preparation method, a method of utilizing metal catalysis is provided to realize the introduction and regulation of defects in the transition metal oxide nanosheet under low temperature and mild conditions, thereby solving the problems of harsh reaction conditions, the need for reducing agents and the destruction of the nanosheet structure in the existing defect engineering technology. The preparation method is simple and easy and has certain universality. The prepared defect-rich transition metal oxide nanosheet / metal heterojunction catalyst exhibits good photothermal catalytic oxidation of aromatic alcohols to aldehydes for coupled hydrogen production, can simultaneously produce fine chemicals and clean hydrogen energy, effectively utilizes photogenerated electron-hole pairs, avoids the generation of by-products, and improves the economic benefits of the product.
[0007] The technical solution of the present invention is as follows:
[0008] One of the purposes of the present invention is to provide a method for preparing defect-rich transition metal oxide nanosheets / metal heterojunction catalysts, wherein the preparation method utilizes metal catalysis to introduce and regulate defects in transition metal oxide nanosheets by controlling the metal precursor content and the illumination time under low temperature conditions.
[0009] Furthermore, the preparation method is as follows:
[0010] S1, grinding and mixing carbonate and transition metal oxide according to a certain molar ratio, and calcining at high temperature in a muffle furnace using a high temperature solid phase method to obtain a transition metal carbonate compound;
[0011] S2, weighing a transition metal carbonate compound and dispersing it into a strong acid solution to perform a proton exchange reaction, then centrifugally washing it until it is neutral, and drying it to obtain a layered transition metal oxide;
[0012] S3, weighing layered transition metal oxide and tetrabutylammonium hydroxide in a certain molar ratio and placing them in a blue-capped bottle, diluting with water to 1 L and stirring, and collecting the upper layer of liquid after centrifugation, i.e., transition metal oxide nanosheets;
[0013] S4, adding the acid solution dropwise into the transition metal oxide nanosheets, stirring and centrifuging to collect the precipitate, washing the precipitate with deionized water until it is neutral, and redispersing it in deionized water to obtain a transition metal oxide nanosheet suspension;
[0014] S5. Mix methanol, water and a transition metal oxide nanosheet suspension, add a metal precursor solution, introduce an inert gas after ultrasonic treatment, and irradiate with ultraviolet light to obtain a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst.
[0015] Furthermore, the carbonate in S1 is one or more of K2CO3, Li2CO3, and Cs2CO3, the transition metal oxide is one or two of Nb2O5 and WO3, the calcination temperature is 800-1000°C, and the calcination time is 5-10h.
[0016] Furthermore, the strong acid solution in S2 is HNO3 with a concentration of 3-6M or HCl with a concentration of 1-3M, and the proton exchange reaction time is 3-8 days.
[0017] Furthermore, the molar ratio of the layered transition metal oxide to tetrabutylammonium hydroxide in S3 is 1:1-1:3.
[0018] Furthermore, the acid solution in S4 is HNO3 with a concentration of 1-3M or HCl with a concentration of 1-3M.
[0019] Furthermore, the transition metal oxide nanosheets in S5 are HNb3O8 or HNbWO6, the thickness of the nanosheets is 1-3 nm, and the concentration of the nanosheet suspension is 10-50 mg mL -1 .
[0020] Furthermore, the metal precursor solution in S5 is one of H2PtCl6·6H2O, H2PdCl4, and RuCl3, with a concentration of 5-20 mg mL -1 , the UV irradiation time is 10-120min.
[0021] A second object of the present invention is to provide a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst.
[0022] The third object of the present invention is to provide an application of a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which is applied to the field of photothermal catalytic selective oxidation of aromatic alcohol compounds to aldehyde coupled hydrogen production, and can simultaneously produce fine chemicals and clean hydrogen energy, effectively utilizing photogenerated electron-hole pairs.
[0023] Compared with the prior art, the beneficial effects of the present invention are:
[0024] 1. Traditional defect engineering mainly involves high-temperature H2 atmosphere calcination, plasma activation, and strong reducing agent reduction. The preparation method of the present invention uses metal catalysis to introduce and regulate defects. In this process, no external reducing agent is required, the reaction conditions are mild, and the equipment is simple, which is conducive to large-scale promotion and has universality.
[0025] 2. The preparation method of defect-rich transition metal oxide nanosheets / metal heterojunction catalysts in the present invention has mild reaction conditions, which avoids the adverse effects of high temperature conditions in traditional preparation methods on nanosheets, so that the nanosheet structure can remain intact and avoid agglomeration and breakage.
[0026] 3. The defect-rich transition metal oxide nanosheet / metal heterojunction catalyst prepared by the present invention has a light absorption range extended to the full spectrum range (250-2500nm), which can achieve effective separation of photogenerated carriers and has a good light-to-heat conversion effect, thereby achieving efficient utilization of solar energy. The defect-rich transition metal oxide nanosheet / metal heterojunction catalyst prepared by the present invention introduces defects, so that the light absorption range is extended to the full spectrum range (250-2500nm). At the same time, the formation of defects and metal heterojunctions leads to effective separation of photogenerated carriers, has a good light-to-heat conversion effect, and achieves efficient utilization of solar energy.
[0027] 4. The defect-rich transition metal oxide nanosheet / metal heterojunction catalyst prepared by the present invention is applied to the field of photothermal catalytic selective oxidation of aromatic alcohol compounds to aldehyde-coupled hydrogen production. Aromatic alcohol is used as the reaction substrate in the reaction, and no sacrificial agent is required. Under illumination conditions, the holes generated by ultraviolet light excite the nanosheets to oxidize alcohol molecules to generate corresponding aldehyde molecules and protons. At the same time, the photogenerated electrons reduce the generated protons to generate hydrogen. At the same time, the thermal effect generated by visible-infrared light accelerates the separation of photogenerated carriers and the oxidation-reduction process, thereby achieving photothermal synergy. This application can simultaneously produce fine chemicals and clean hydrogen energy, effectively utilize photogenerated electron-hole pairs, avoid the generation of by-products, and improve the economic benefits of the product.
[0028] Reference numerals
[0029] Figure 1This is an atomic force microscope image of the 1.5wt% Pt / HNb3O8 catalyst synthesized in Example 1 of the present invention;
[0030] Figure 2 The electron paramagnetic resonance spectra of the Pt / HNb3O8 catalyst and HNb3O8 synthesized in Examples 1-8 of the present invention;
[0031] Figure 3 The results of the activity test of the Pt / HNb3O8 catalyst in Examples 10-11 of the present invention;
[0032] Figure 4 These are the test results of the Pt / HNb3O8 catalyst activity in Examples 12-13 of the present invention. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the accompanying drawings and preferred embodiments. The given embodiments are only for illustrating the present invention, rather than for limiting the scope of the present invention.
[0034] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources;
[0035] The quantitative tests in the following examples were repeated three times, and the results were averaged.
[0036] The experimental methods in the following embodiments are conventional methods unless otherwise specified.
[0037] Example 1 Preparation of 1.5wt% Pt / HNb3O8 Catalyst
[0038] This embodiment provides a method for preparing a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which specifically includes the following steps:
[0039] S1. Weigh 0.03 mol of Nb2O5 and 0.011 mol of K2CO3, grind them evenly and transfer them to a crucible. Calcine them at 800°C for 5 h, cool them to room temperature and collect KNb3O8.
[0040] S2, weigh 8g KNb3O8 and disperse it in HNO3 solution (3M) and stir vigorously for 3 days, collect the precipitate by centrifugation and wash it with deionized water until neutral, and collect it after drying to obtain layered HNb3O8;
[0041] S3, weigh 2g of layered HNb3O8 and 2g of TBAOH (tetrabutylammonium hydroxide, 56%) solution, mix them in a blue-capped bottle, dilute to 1L with deionized water, stir vigorously for 14 days, and collect the upper layer solution by centrifugation;
[0042] S4. Add an equal volume of HNO3 solution (1M) to the upper solution, collect the precipitate, wash it with deionized water until it is neutral, and redisperse it in deionized water to obtain 10 mg mL -1 HNb3O8 nanosheet colloidal solution;
[0043] S5, take 50 mg of HNb3O8 nanosheet colloidal solution, dilute it to 8 mL with deionized water, add 8 mL of methanol and transfer it to a quartz reactor, and transfer 199.1 μL of 10 mg mL -1 H2PtCl6·6H2O was added dropwise to the mixed solution and dispersed evenly by ultrasonication to make the Pt loading amount 1.5wt%. Argon was continuously introduced for 20 min to remove the air in the solution and the solution was sealed;
[0044] S6. The solution prepared in S5 was irradiated with ultraviolet light for 90 minutes at room temperature. The black product was collected by centrifugation and washed three times with deionized water to obtain a catalyst of 1.5 wt% Pt / HNb3O8.
[0045] Figure 1 The atomic force microscope (AFM) image of the catalyst 1.5wt% Pt / HNb3O8 synthesized by the preparation method is shown; Figure 1 It can be seen that the thickness of the nanosheets after defects are introduced by Pt loading in the present invention is maintained at about 2 nm, successfully avoiding the stacking and agglomeration of the nanosheets.
[0046] Example 2 Preparation of 0.5wt% Pt / HNb3O8 Catalyst
[0047] This embodiment provides a method for preparing a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which specifically includes the following steps:
[0048] S1. Weigh 0.03 mol of Nb2O5 and 0.011 mol of K2CO3, grind them evenly and transfer them to a crucible. Calcine them at 900°C for 7 h, cool them to room temperature and collect KNb3O8.
[0049] S2, weigh 8g KNb3O8 and disperse it in HNO3 solution (4M) and stir vigorously for 6 days, collect the precipitate by centrifugation and wash it with deionized water until neutral, and collect it after drying to obtain layered HNb3O8;
[0050] S3, weigh 2g of layered HNb3O8 and 4g of TBAOH (tetrabutylammonium hydroxide, 56%) solution, mix them in a blue-capped bottle, dilute to 1L with deionized water, stir vigorously for 14 days, and collect the upper solution by centrifugation;
[0051] S4. Add an equal volume of HNO3 solution (1M) to the upper solution, collect the precipitate, wash it with deionized water until it is neutral, and redisperse it in deionized water to obtain 10 mg mL -1 HNb3O8 nanosheet colloidal solution;
[0052] S5, take 50 mg HNb3O8 nanosheet colloidal solution, dilute it to 8 mL with deionized water, add 8 mL methanol and transfer it to a quartz reactor. -1 H2PtCl6·6H2O was added dropwise to the mixed solution and dispersed evenly by ultrasonication to make the Pt loading amount 0.5wt%. Argon was continuously introduced for 20 min to remove the air in the solution and the solution was sealed;
[0053] S6. The solution prepared in S5 was irradiated with ultraviolet light for 90 minutes at room temperature. The black product was collected by centrifugation and washed with deionized water for 4 times to obtain a catalyst of 0.5 wt% Pt / HNb3O8.
[0054] Example 3 Preparation of 1.0wt% Pt / HNb3O8 Catalyst
[0055] This embodiment provides a method for preparing a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which specifically includes the following steps:
[0056] S1. Weigh 0.03 mol of Nb2O5 and 0.011 mol of K2CO3, grind them evenly and transfer them to a crucible. Calcine them at 900°C for 10 h, cool them to room temperature and collect KNb3O8.
[0057] S2, weigh 8g KNb3O8 and disperse it in HNO3 solution (6M) and stir vigorously for 6 days, collect the precipitate by centrifugation and wash it with deionized water until neutral, and collect it after drying to obtain layered HNb3O8;
[0058] S3, weigh 2g of layered HNb3O8 and 4g of TBAOH (tetrabutylammonium hydroxide, 56%) solution, mix them in a blue-capped bottle, dilute to 1L with deionized water, stir vigorously for 14 days, and collect the upper solution by centrifugation;
[0059] S4. Add an equal volume of HNO3 solution (2M) to the upper solution, collect the precipitate, wash it with deionized water until it is neutral, and redisperse it in deionized water to obtain 30 mg mL -1 HNb3O8 nanosheet colloidal solution;
[0060] S5, take 50 mg of HNb3O8 nanosheet colloidal solution, dilute it to 8 mL with deionized water, add 8 mL of methanol and transfer it to a quartz reactor, and transfer 132.8 μL of 10 mg mL -1H2PtCl6·6H2O was added dropwise to the mixed solution and dispersed evenly by ultrasonication to make the Pt loading amount 1.0wt%. Argon was continuously introduced for 20 min to remove the air in the solution and the solution was sealed;
[0061] S6. The solution prepared in S5 was irradiated with ultraviolet light for 90 minutes at room temperature. The black product was collected by centrifugation and washed with deionized water for 4 times to obtain a catalyst of 1.0 wt% Pt / HNb3O8.
[0062] Example 4 Preparation of 2.0wt% Pt / HNb3O8 Catalyst
[0063] This embodiment provides a method for preparing a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which specifically includes the following steps:
[0064] S1. Weigh 0.03 mol of Nb2O5 and 0.011 mol of K2CO3, grind them evenly and transfer them to a crucible. Calcine them at 1000°C for 10 h, cool them to room temperature and collect KNb3O8.
[0065] S2, weigh 8g KNb3O8 and disperse it in HNO3 solution (6M) and stir vigorously for 8 days, collect the precipitate by centrifugation and wash it with deionized water until neutral, and collect it after drying to obtain layered HNb3O8;
[0066] S3, weigh 2g of layered HNb3O8 and 6g of TBAOH (tetrabutylammonium hydroxide, 56%) solution, mix them in a blue-capped bottle, dilute to 1L with deionized water, stir vigorously for 14 days, and collect the upper layer solution by centrifugation;
[0067] S4. Add an equal volume of HNO3 solution (3M) to the upper solution, collect the precipitate, wash it with deionized water until it is neutral, and redisperse it in deionized water to obtain 50 mg mL -1 HNb3O8 nanosheet colloidal solution;
[0068] S5, take 50 mg HNb3O8 nanosheet colloidal solution, dilute it to 8 mL with deionized water, add 8 mL methanol and transfer it to a quartz reactor. -1 H2PtCl6·6H2O was added dropwise to the mixed solution and dispersed evenly by ultrasonication to make the Pt loading amount 2.0wt%. Argon was continuously introduced for 20min to remove the air in the solution and the solution was sealed;
[0069] S6. The solution prepared in S5 was irradiated with ultraviolet light for 90 minutes at room temperature. The black product was collected by centrifugation and washed with deionized water for 5 times to obtain a catalyst of 2.0 wt% Pt / HNb3O8.
[0070] Example 5 Preparation of Pt / HNb3O8-10 Catalyst
[0071] This embodiment provides a method for preparing a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which specifically includes the following steps:
[0072] S1. Weigh 0.03 mol of Nb2O5 and 0.011 mol of K2CO3, grind them evenly and transfer them to a crucible. Calcine them at 800°C for 5 h, cool them to room temperature and collect KNb3O8.
[0073] S2, weigh 8g KNb3O8 and disperse it in HNO3 solution (3M) and stir vigorously for 3 days, collect the precipitate by centrifugation and wash it with deionized water until neutral, and collect it after drying to obtain layered HNb3O8;
[0074] S3, weigh 2g of layered HNb3O8 and 2g of TBAOH (tetrabutylammonium hydroxide, 56%) solution, mix them in a blue-capped bottle, dilute to 1L with deionized water, stir vigorously for 14 days, and collect the upper layer solution by centrifugation;
[0075] S4. Add an equal volume of HNO3 solution (1M) to the upper solution, collect the precipitate, wash it with deionized water until it is neutral, and redisperse it in deionized water to obtain 10 mg mL -1 HNb3O8 nanosheet colloidal solution;
[0076] S5, take 50 mg of HNb3O8 nanosheet colloidal solution, dilute it to 8 mL with deionized water, add 8 mL of methanol and transfer it to a quartz reactor, and transfer 199.1 μL of 10 mg mL -1 H2PtCl6·6H2O was added dropwise to the mixed solution and dispersed evenly by ultrasonication to make the Pt loading amount 2.0wt%. Argon was continuously introduced for 20min to remove the air in the solution and the solution was sealed;
[0077] S6. The solution prepared in S5 was irradiated with ultraviolet light for 10 min at room temperature. The black product was collected by centrifugation and washed with deionized water for three times to obtain the catalyst Pt / HNb3O8-10.
[0078] Example 6 Preparation of Pt / HNb3O8-30 Catalyst
[0079] This embodiment provides a method for preparing a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which specifically includes the following steps:
[0080] S1. Weigh 0.03 mol of Nb2O5 and 0.011 mol of K2CO3, grind them evenly and transfer them to a crucible. Calcine them at 900°C for 7 h, cool them to room temperature and collect KNb3O8.
[0081] S2, weigh 8g KNb3O8 and disperse it in HNO3 solution (4M) and stir vigorously for 6 days, collect the precipitate by centrifugation and wash it with deionized water until neutral, and collect it after drying to obtain layered HNb3O8;
[0082] S3, weigh 2g of layered HNb3O8 and 4g of TBAOH (tetrabutylammonium hydroxide, 56%) solution, mix them in a blue-capped bottle, dilute to 1L with deionized water, stir vigorously for 14 days, and collect the upper solution by centrifugation;
[0083] S4. Add an equal volume of HNO3 solution (1M) to the upper solution, collect the precipitate, wash it with deionized water until it is neutral, and redisperse it in deionized water to obtain 10 mg mL -1 HNb3O8 nanosheet colloidal solution;
[0084] S5, take 50 mg of HNb3O8 nanosheet colloidal solution, dilute it to 8 mL with deionized water, add 8 mL of methanol and transfer it to a quartz reactor, and transfer 199.1 μL of 10 mg mL -1 H2PtCl6·6H2O was added dropwise to the mixed solution and dispersed evenly by ultrasonication to make the Pt loading amount 2.0wt%. Argon was continuously introduced for 20min to remove the air in the solution and the solution was sealed;
[0085] S6. The solution prepared in S5 was irradiated with ultraviolet light for 30 minutes at room temperature. The black product was collected by centrifugation and washed with deionized water for 4 times to obtain the catalyst Pt / HNb3O8-30.
[0086] Example 7 Preparation of Pt / HNb3O8-60 Catalyst
[0087] This embodiment provides a method for preparing a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which specifically includes the following steps:
[0088] S1. Weigh 0.03 mol of Nb2O5 and 0.011 mol of K2CO3, grind them evenly and transfer them to a crucible. Calcine them at 900°C for 10 h, cool them to room temperature and collect KNb3O8.
[0089] S2, weigh 8g KNb3O8 and disperse it in HNO3 solution (6M) and stir vigorously for 6 days, collect the precipitate by centrifugation and wash it with deionized water until neutral, and collect it after drying to obtain layered HNb3O8;
[0090] S3, weigh 2g of layered HNb3O8 and 4g of TBAOH (tetrabutylammonium hydroxide, 56%) solution, mix them in a blue-capped bottle, dilute to 1L with deionized water, stir vigorously for 14 days, and collect the upper solution by centrifugation;
[0091] S4. Add an equal volume of HNO3 solution (2M) to the upper solution, collect the precipitate, wash it with deionized water until it is neutral, and redisperse it in deionized water to obtain 30 mg mL -1 HNb3O8 nanosheet colloidal solution;
[0092] S5, take 50 mg of HNb3O8 nanosheet colloidal solution, dilute it to 8 mL with deionized water, add 8 mL of methanol and transfer it to a quartz reactor, and transfer 199.1 μL of 10 mg mL -1 H2PtCl6·6H2O was added dropwise to the mixed solution and dispersed evenly by ultrasonication to make the Pt loading amount 2.0wt%. Argon was continuously introduced for 20min to remove the air in the solution and the solution was sealed;
[0093] S6. The solution prepared in S5 was irradiated with ultraviolet light for 60 min at room temperature. The black product was collected by centrifugation and washed with deionized water for 4 times to obtain the catalyst Pt / HNb3O8-60.
[0094] Example 8 Preparation of Pt / HNb3O8-120 Catalyst
[0095] This embodiment provides a method for preparing a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which specifically includes the following steps:
[0096] S1. Weigh 0.03 mol of Nb2O5 and 0.011 mol of K2CO3, grind them evenly and transfer them to a crucible. Calcine them at 1000°C for 10 h, cool them to room temperature and collect KNb3O8.
[0097] S2, weigh 8g KNb3O8 and disperse it in HNO3 solution (6M) and stir vigorously for 8 days, collect the precipitate by centrifugation and wash it with deionized water until neutral, and collect it after drying to obtain layered HNb3O8;
[0098] S3, weigh 2g of layered HNb3O8 and 6g of TBAOH (tetrabutylammonium hydroxide, 56%) solution, mix them in a blue-capped bottle, dilute to 1L with deionized water, stir vigorously for 14 days, and collect the upper layer solution by centrifugation;
[0099] S4. Add an equal volume of HNO3 solution (3M) to the upper solution, collect the precipitate, wash it with deionized water until it is neutral, and redisperse it in deionized water to obtain 50 mg mL -1 HNb3O8 nanosheet colloidal solution;
[0100] S5, take 50 mg of HNb3O8 nanosheet colloidal solution, dilute it to 8 mL with deionized water, add 8 mL of methanol and transfer it to a quartz reactor, and transfer 199.1 μL of 10 mg mL-1 H2PtCl6·6H2O was added dropwise to the mixed solution and dispersed evenly by ultrasonication to make the Pt loading amount 2.0wt%. Argon was continuously introduced for 20min to remove the air in the solution and the solution was sealed;
[0101] S6. The solution prepared in S5 was irradiated with ultraviolet light for 120 min at room temperature. The black product was collected by centrifugation and washed with deionized water for 5 times to obtain the catalyst Pt / HNb3O8-120.
[0102] The HNb3O8 and related catalysts Pt / HNb3O8 prepared in Examples 1-8 were analyzed by electron paramagnetic resonance spectrometer (EPR) to obtain the following: Figure 2 The EPR spectra shown in the figure show that the prepared Pt / HNb3O8 all show similar EPR signals at g=2.003, which is generally considered to be the characteristic value of oxygen vacancies, proving that defects have been successfully introduced. In addition, the concentration of defects in the nanosheets can be controlled by simply adjusting the metal precursor content and the illumination time.
[0103] Example 9 Preparation of 1.5wt% Pd / HNbWO6 Catalyst
[0104] This embodiment provides a method for preparing a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, which specifically includes the following steps:
[0105] S1. Weigh 0.04 mol WO3, 0.02 mol Nb2O5 and 0.021 mol Li2CO3, grind them evenly and transfer them to a crucible. Sinter them at 800°C for 10 h and cool them to room temperature to obtain LiNbWO6.
[0106] S2, weigh 8 g of LiNbWO6 and disperse it in HNO3 solution (6M) and stir vigorously for 6 days, collect the precipitate by centrifugation and wash it with deionized water until neutral, and then dry it to obtain layered HNbWO6;
[0107] S3, weigh 2g of layered HNbWO6 and 4g of TBAOH (tetrabutylammonium hydroxide, 56%) in a blue-capped bottle, mix the solution, dilute to 1L with deionized water, stir vigorously for 14 days, and collect the upper layer solution by centrifugation;
[0108] S4. Add an equal volume of HNO3 solution (1M) to the upper solution, collect the precipitate, wash it with deionized water until it is neutral, and redisperse it in deionized water to obtain 10 mg mL -1 HNbWO6 nanosheet colloidal solution;
[0109] S5, take 50 mg HNbWO6 nanosheet colloidal solution, dilute it to 8 mL with deionized water, add 8 mL methanol and transfer it to a quartz reactor, and transfer 117.6 μL 10 mg mL -1 H2PdCl4 was added dropwise to the mixed solution and ultrasonic dispersion was continued to be uniform, so that the Pd loading amount was 1.5wt%. Argon was continuously introduced for 20 min to remove the air in the solution and the solution was sealed;
[0110] S6. The solution prepared in S5 was irradiated with ultraviolet light for 90 minutes at room temperature. The black product was collected by centrifugation and washed with deionized water for three times to obtain a catalyst of 1.5 wt% Pd / HNbWO6.
[0111] Example 10 Photocatalytic selective oxidation of benzyl alcohol coupled to hydrogen production experiment
[0112] 10 mg of x wt% Pt / HNb3O8 (x = 0.5, 1.0, 1.5, 2.0) and HNb3O8 catalyst prepared in Examples 1 to 4 were dispersed in 3 mL of acetonitrile, 0.1 mmol of benzyl alcohol was added, and the reaction mixture was transferred to a 20 mL quartz reactor and sealed with a rubber stopper. Argon was used at 80 mL min -1 The flow rate was maintained in the dark for 30 min to completely remove air;
[0113] A xenon lamp equipped with a 365 nm bandpass filter was used as the UV light source. After continuous irradiation for 2 h, the liquid product was analyzed by a gas chromatograph equipped with FID (GC-2030, Shimadzu, Japan), and the gas product was analyzed by a gas chromatograph equipped with TCD (GC-2030, Shimadzu, Japan).
[0114] Example 11 Experiment on photocatalytic selective oxidation of benzyl alcohol coupled to produce hydrogen
[0115] 10 mg of x wt% Pt / HNb3O8 (x = 0.5, 1.0, 1.5, 2.0) and HNb3O8 catalyst prepared in Examples 1 to 4 were dispersed in 3 mL of acetonitrile, 0.1 mmol of benzyl alcohol was added, and the reaction mixture was transferred to a 20 mL quartz reactor and sealed with a rubber stopper. Argon was used at 80 mL min -1 The flow rate was maintained in the dark for 30 min to completely remove air;
[0116] A xenon lamp equipped with a 365 nm bandpass filter was used as the UV light source, and a xenon lamp equipped with a 400 nm cutoff filter was used as the visible-infrared light source for heating. After continuous irradiation for 2 h, the liquid product was analyzed by a gas chromatograph equipped with FID (GC-2030, Shimadzu, Japan), and the gas product was analyzed by a gas chromatograph equipped with TCD (GC-2030, Shimadzu, Japan).
[0117] The test results of Examples 10-11 are as follows Figure 3 As shown; the Pt / HNb3O8 catalyst shows good photothermal catalytic activity, indicating that Pt / HNb3O8 can efficiently utilize solar energy for the selective oxidation of benzyl alcohol to aldehyde coupling to produce hydrogen.
[0118] Example 12 Photocatalytic selective oxidation of aromatic alcohols coupled to produce hydrogen
[0119] 10 mg of x wt% Pt / HNb3O8 (x = 0.5, 1.0, 1.5, 2.0) and HNb3O8 catalyst prepared in Examples 1 to 4 were dispersed in 3 mL of acetonitrile, 0.1 mmol of a series of aromatic alcohol reactants were added, and then transferred to a 20 mL quartz reactor and sealed with a rubber stopper. Argon was used at 80 mL min -1 The flow rate was maintained in the dark for 30 min to completely remove air;
[0120] A xenon lamp equipped with a 365 nm bandpass filter was used as the UV light source. After continuous irradiation for 2 h, the liquid product was analyzed by a gas chromatograph equipped with FID (GC-2030, Shimadzu, Japan), and the gas product was analyzed by a gas chromatograph equipped with TCD (GC-2030, Shimadzu, Japan).
[0121] Example 13 Photocatalytic selective oxidation of aromatic alcohols coupled to produce hydrogen
[0122] 10 mg of x wt% Pt / HNb3O8 (x = 0.5, 1.0, 1.5, 2.0) and HNb3O8 catalyst prepared in Examples 1 to 4 were dispersed in 3 mL of acetonitrile, 0.1 mmol of a series of aromatic alcohol reactants were added, and then transferred to a 20 mL quartz reactor and sealed with a rubber stopper. Argon was used at 80 mL min -1 The flow rate was maintained in the dark for 30 min to completely remove air;
[0123] A xenon lamp equipped with a 365 nm bandpass filter was used as the UV light source, and a xenon lamp equipped with a 400 nm cutoff filter was used as the visible-infrared light source for heating. After continuous irradiation for 2 h, the liquid product was analyzed by a gas chromatograph equipped with FID (GC-2030, Shimadzu, Japan), and the gas product was analyzed by a gas chromatograph equipped with TCD (GC-2030, Shimadzu, Japan).
[0124] The test results of Examples 12-13 are as follows Figure 4 As shown; Pt / HNb3O8 catalyst shows good photothermal catalytic activity, indicating that Pt / HNb3O8 can efficiently utilize solar energy for selective oxidation of aromatic alcohol compounds to aldehyde coupling and hydrogen production.
[0125] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing defect-rich transition metal oxide nanosheets / metal heterojunction catalysts, characterized in that: The preparation method is to use metal catalysis to control the metal precursor content and light exposure time under low temperature conditions to introduce and regulate defects in transition metal oxide nanosheets, and specifically includes the following steps: S1, grinding and mixing carbonate and transition metal oxide according to a certain molar ratio, and calcining at high temperature in a muffle furnace using a high temperature solid phase method to obtain a product; S2, weighing the product obtained in S1, dispersing it into a strong acid solution for proton exchange reaction, then centrifugally washing it until it is neutral, and drying it to obtain a layered transition metal oxide; S3, weighing layered transition metal oxides and tetrabutylammonium hydroxide in a certain molar ratio and placing them in a blue-capped bottle, diluting them to 1 L with water and stirring, and collecting the upper liquid after centrifugation; S4, adding the acid solution dropwise into the upper layer liquid collected in S3, stirring and centrifuging to collect the precipitate, washing the precipitate with deionized water until it is neutral, and redispersing it in deionized water to obtain a transition metal oxide nanosheet suspension; S5, mixing an equal volume of a transition metal oxide nanosheet suspension and methanol, adding a metal precursor solution, introducing an inert gas after ultrasonic treatment, and irradiating with ultraviolet light to obtain a defect-rich transition metal oxide nanosheet / metal heterojunction catalyst; The carbonate in S1 is one or more of K2CO3, Li2CO3, and Cs2CO3, the transition metal oxide is Nb2O5 or Nb2O5 and WO3, the calcination temperature is 800-1000°C, and the calcination time is 5-10 h; The strong acid solution in S2 is a 3-6 M HNO3 solution or a 1-3 M HCl solution, and the proton exchange reaction time is 3-8 days; The molar ratio of the layered transition metal oxide to tetrabutylammonium hydroxide in S3 is 1:1-1:3; The acid solution in S4 is a HNO3 solution with a concentration of 1-3 M or a HCl solution with a concentration of 1-3 M; The transition metal oxide nanosheets in S5 are HNb3O8 or HNbWO6, the thickness of the nanosheets is 1-3 nm, and the concentration of the nanosheet suspension is 10-50 mg / mL; The metal precursor solution in S5 is one of H2PtCl6·6H2O, H2PdCl4, and RuCl3, with a concentration of 5-20 mg / mL, the loaded metal is one of Pt, Pd, and Ru, with a loading ratio of 0.5-2.0 wt%, and the ultraviolet light irradiation time is 10-120 min.
2. A defect-rich transition metal oxide nanosheet / metal heterojunction catalyst prepared according to the method of claim 1.
3. An application of defect-rich transition metal oxide nanosheet / metal heterojunction catalyst, characterized in that: The defect-rich transition metal oxide nanosheet / metal heterojunction catalyst described in claim 2 is applied to the photothermal catalytic selective oxidation reaction of aromatic alcohol compounds into aldehydes and hydrogen.
Citation Information
Patent Citations
Flaky molybdenum dixarbide / transition metal heterojunction electro-catalysis composite material and preparation method thereof
CN110180569A
Defect-rich Co3S4 ultra-thin porous nanosheet material and preparation method and application thereof
CN110404562A
Pd / niobate nanosheet catalyst as well as preparation method and application thereof
CN104549263A
Monolayer HNbWO6 nanosheet preparation method
CN104860354A